The United States and Canadian National Industrial Conferences of 1919: A Comparative Analysis - Gerber, Larry G. (Labor History, 1991)
Presents a comparison of the National Industrial Conferences of the US and Canada which were held in 1919 for the purpose of making postwar labor-management relations more harmonious. While the Armistice of November 1918 halted fighting between nations in "the war to end all wars," industrial "warfare" between labor and capital soon erupted in many countries of the world. In 1919, the U.S. and Canada both experienced a higher level of strike activity than ever before. The outbreak of widely publicized general strikes in Seattle and Winnipeg even caused some Americans and Canadians to believe that revolution might be in the offing.' Faced with this turmoil, the heads of government in the U. S. and Canada sought to achieve peace by calling upon the warring parties in industry to send representatives to National industrial Conferences whose purpose was to achieve a consensus about how to make postwar labor-management relations more harmonious. Months before either the U.S. or Canadian governments convened their National Industrial Conferences, the British government had successfully utilized what David Lloyd George described as a "Peace Congress" of employer and trade union representatives to help cairn postwar labor unrest in Great Britain.